Analisis Semiotika Representasi Isu Toxic Masculinity dalam Film “Seperti Dendam, Rindu Harus Dibayar Tuntas” - Aditya Kusuma, Bima; Hartono, Aurelia Lintang Pramesti; Setyarahajoe, Ratna (Kinesik, 2024)
This article aims to describe the representation of toxic masculinity in the film "Seperti Dendam Harus Dibayar Tuntas". This research uses a descriptive qualitative approach and the technique of semiotics data analysis from the John Fiske model. There are three levels of encoding in this model: realities, level representation, and level ideology. The results show that the representation of toxic masculinity depicted by the main characters can be seen at the level of realities in the category of costume. The representation is also shown through medium shot, close-up, two-shot, and over-the-shoulder shot in level representation. Level ideology is shown by Ajo Kawir's high individualism, which includes a superiority complex, acting for personal interests, and a tough head. The toxic masculinity of the main characters is influenced by past trauma and the patriarchal society. Level realities of social coding are shown through costumes, speech patterns, and expressions. Level representation of social coding is shown through camera angles and lighting. Level ideology of social coding is shown through actions, dialogues, and characters.